PENGARUH MANAJEMEN MODAL KERJA TERHADAP KINERJA PERUSAHAAN SEKTOR NON KEUANGAN - Hayundaniswara, Allgamanora; Faisal (APSSAI ACCOUNTING REVIEW, 2022)
The study examines the correlation between working capital management, profitability, firm value, and stock return volatility. The sample consists of 115 non-financial companies listed on the Bloomberg database in 2018. The results reveal that networking capital has a negative and significant effect on profitability, firm value and stock return volatility, indicating that managers need to make decisions to increase their profitability while controlling risk. The results contribute to the literature on the role of working capital in profitability, firm value, and stock return volatility. It also provides benefits to related managerial managers considering working capital management to overcome the trade-off decisions to increase profitability while reducing the company's potential risk.